Mutations in the SMAD4/DPC4 gene in juvenile polyposis. - Howe, JR; Roth, S; Ringold, J; Summers, R; Järvinen, H; Sistonen, P; Tomlinson, I; Houlston, R; Bevan, S; Mitros, F; Stone, E; Aaltonen, L (1998)
Familial juvenile polyposis is an autosomal dominant disease characterized by a predisposition to hamartomatous polyps and gastrointestinal cancer. Here it is shown that a subset of juvenile polyposis families carry germ line mutations in the gene SMAD4 (also known as DPC4), located on chromosome 18q21.1, that encodes a critical cytoplasmic mediator in the transforming growth factor-beta signaling pathway. The mutant SMAD4 proteins are predicted to be truncated at the carboxyl-terminus and lack sequences required for normal function. These results confirm an important role for SMAD4 in the development of gastrointestinal tumors.